Increase your reading power a handbook workbook reading comprehension builders - Avalos, Adelaida G. (Manila Rex Book Store, 1996)
"This instructional material is designed to enable students to increase their reading comprehension in the four cognitive processes: literal, analytical, evaluative, and integrative thinking. Specifically, its target users are students who missed a clear understanding of the basic principles of learning the English language and a substantial training on their uses as they relate to the reading process. It is divided into two major parts : Part one, is entitled "Fundamentals of reading", which provides for the sharpening of the sentence sense through structural and semantic analysis as applied in percieving relationships in and between interconnected words, phrases, clauses, and sentences. Part Two is entitled "Application Level-Reading Comprehension Builders." All the formulated concepts and understanding are put to use in the reading dimension. Learners are immersed in the analysis and synthesis of idea units at the sentence, paragraph, and longer discourse levels."--Preface.
Keywords: Reading comprehension; Reading (Higher Education).